1992
DOI: 10.1002/elan.1140040807
|View full text |Cite
|
Sign up to set email alerts
|

Stripping measurements of hydrogen peroxide based on biocatalytic accumulation at mediatorless peroxidase/carbon paste electrodes

Abstract: Biocatalytic accumulation. followed by chronoamperometric detection, is shown to greatly enhance the sensitivity of mediatorless biosensing of hydrogen peroxide at horseradish peroxidase (HW)/carbon paste bioelectrodes. The mixed carbon paste, with its close proximity between the biocatalytic and graphite sensing sites, promotes the mediatorless accumulation of the oxidized form of HRP. Hence, a 2&fold enhancement of the response for 10 p M hydrogen peroxide is obtained following 3-minute preconcentration. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…[11][12][13] The use of crude extract rather than isolated enzymes represents not only alternative and attractive analytical properties, but also simplicity, stability, longer lifetime, lower cost and reduced co-factor requirements. 19,20,36 Figure 1 shows a scheme of the enzymatic processes between catecholamine (adrenaline or dopamine) and laccase (PPO) of crude extract incorporated into a carbon paste electrode.…”
Section: Principle Of Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13] The use of crude extract rather than isolated enzymes represents not only alternative and attractive analytical properties, but also simplicity, stability, longer lifetime, lower cost and reduced co-factor requirements. 19,20,36 Figure 1 shows a scheme of the enzymatic processes between catecholamine (adrenaline or dopamine) and laccase (PPO) of crude extract incorporated into a carbon paste electrode.…”
Section: Principle Of Measurementsmentioning
confidence: 99%
“…10 In addition to purified enzymes, [11][12][13] animal, 14 and vegetable extracts, [15][16][17][18] immobilized on the electrode surface by different methods, have also been employed as catalyst sources in both aqueous and organic solutions. Carbon paste electrodes have been widely used owing to the possibility of immobilizing not only enzymes, but also ligands, redox mediators, biological tissues, to catalyze the oxidation/reduction of compounds involved in enzymatic reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Many methods such as titrimetry, UV-vis spectrophotometry and electrochemistry have been developed for this purpose [1][2][3]. Among these methods, the amperometric biosensors based on the direct electron transfer between an electrode and the immobilized enzyme/protein is especially promising because of its simplicity and high sensitivity [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Horseradish peroxidase (HRP), a prototypical hemeprotein peroxidase (FW ca.…”
Section: Introductionmentioning
confidence: 99%
“…The recorded current will then be proportional to the glucose concentration in the sample. Previously it has been clearly shown that using polymeric bound mediators and especially polymeric mediators covalently bound with the enzyme is beneficial to obtain stable biosensors [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]. However, in the case stipulated in this work when coimmobilising GOD and HRP it has been possible to achieve long term stable sensors.…”
Section: Resultsmentioning
confidence: 99%
“…The synergetIc effect of redox mediators and peroxidase in a bienzymatic biosensor for glucose assays in FIA (HRP) coupled with ferrocene have been reported [48][49][50][51][52][53].…”
mentioning
confidence: 99%